Associations of thyroid hormones with chronic diarrhea and constipation in euthyroid individuals - Zeng, Weiwei; Wang, Yanjun; Zhang, Luofang (Frontiers in Endocrinology, 2024)
Background: Abnormalities in thyroid function affect bowel health. However, the relationships between thyroid hormone concentrations and the risk of developing chronic diarrhea and constipation remain unclear. Thus, the aim of this study was to investigate the relationships between thyroid hormone concentrations and the risk of developing chronic diarrhea and constipation in euthyroid US adults. Methods: The data for this population-based study were taken from the National Health and Nutrition Examination Survey (NHANES) 2007-2010 datasets. The relationships between thyroid hormone concentrations and the risk of developing chronic diarrhea and constipation were examined via multivariate regression. Smoothed curve fitting and threshold effects analysis were used to test for nonlinear relationships and inflection points. Results: This study involved 4999 participants ranging in age from 20 to 80 years. Multivariate logistic regression analysis revealed a significant positive correlation between FT3 concentrations and the risk of developing chronic diarrhea [1.37 (1.00, 1.88), P=0.049]. Multivariate linear regression analysis revealed a significant positive correlation between FT3 concentrations and the number of bowel movements [0.84 (0.39, 1.28), P<0.001]. Using smoothed curve fitting and the two-stage regression model, we found a nonlinear relationship between FT4 concentrations and chronic diarrhea, with a breakpoint of 0.79 ng/dl.Conclusions: There were associations between thyroid hormone concentrations and abnormal bowel habits, particularly between FT3 concentrations and the risk of developing chronic diarrhea. A higher FT3 level was associated with an increased risk of developing chronic diarrhea and more frequent bowel movements. To validate our results, further large-scale prospective studies are needed.